2009
DOI: 10.1182/blood-2008-02-140616
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of follicular lymphoma by array comparative genomic hybridization reveals prognostically significant DNA copy number imbalances

Abstract: The secondary genetic events associated with follicular lymphoma (FL) progression are not well defined. We applied genome-wide BAC array comparative genomic hybridization to 106 diagnostic biopsies of FL to characterize regional genomic imbalances. Using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
95
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 52 publications
13
95
0
Order By: Relevance
“…When comparing by t(14;18) status, we found that cases lacking t(14;18) showed gains in 1q, 3, 14q, and loss in 6q. Similar to Cheung et al, we did not find gains in 18q in our t(14;18) negative cases [6] but we did find gains in chromosome three similar to Tagawa et al [5]. We also found that extranodal FL cases had significant gains 3p, 4q, 7p, and 17p as compared to nodal FL.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…When comparing by t(14;18) status, we found that cases lacking t(14;18) showed gains in 1q, 3, 14q, and loss in 6q. Similar to Cheung et al, we did not find gains in 18q in our t(14;18) negative cases [6] but we did find gains in chromosome three similar to Tagawa et al [5]. We also found that extranodal FL cases had significant gains 3p, 4q, 7p, and 17p as compared to nodal FL.…”
supporting
confidence: 89%
“…We found that in low stage FL the most frequent gains are in chromosomes 1, 6p, 7q, 12p, 15q, X, and 17 while the most frequent deletions are in chromosomes 1q, 17q, and X. Comparison of our results with previous study of 127 FL by CGH method shows overall similar results [6]. Notable difference present in stage I FL cases includes gains in 16p and deletions in 17q.…”
supporting
confidence: 84%
“…Surprisingly, even the degraded archival Pap smear DNAs showed similar structural aberrations as matched DQ samples on Agilent array CGH and Infinium SNP arrays, although with greater background noise. One low-grade follicular lymphoma aspirate clearly manifested (Figure 2A) recentlydescribed poor-prognostic genomic copy number features, 11 while some samples of SCLC showed ( Figure 2B) 18q amplification encompassing BCL-2, an aberration correlated with responsiveness to certain antitumor drugs. 12 Positive identification of gross genomic structural defects in whole slide scrapes of FNAC samples is remarkable, given the potential a priori for low tumor cellular fraction in aspirates.…”
Section: Discussionmentioning
confidence: 99%
“…This comprised the detection of other recurrent genomic structural aberrations including the loss of 4q34-q35, gain of 3p, 3q, and 12q, all of which can be seen in conventional follicular lymphoma, [23][24][25][26] but are detected at higher frequencies in nodal marginal zone lymphomas. 27,28 Gains of 2p (four cases with three as focal gains of REL, at higher frequency than observed in follicular lymphoma), 9q, and 11p were also recurrently observed.…”
Section: Modern Pathology (2016) 29 570-581mentioning
confidence: 99%